Deficiencies in the Recognition and Reporting of Chronic Kidney Disease in Patients With Type 2 Diabetes Mellitus; A Hungarian Nationwide Analysis - Erzsébet Ladányi; Balázs Salfer; József Balla; István Kárpáti; György Reusz; Lilla Szabó; Péter Andriska; László Németh; István Wittmann; Boglárka Laczy (Frontiers Media S.A., 2023)
Objectives: Recognition of chronic kidney disease (CKD) is crucial in type 2 diabetes mellitus (T2DM). We conducted a nationwide epidemiological study to evaluate T2DM-associated CKD in Hungary between 2016 and 2020.Methods: Annual incidence and prevalence rates of registered CKD amongst all pharmacologically treated T2DM patients were analyzed in different age-groups by the central database of the Hungarian Health Insurance Fund Management. Statistical methods included Poisson regression, Bonferroni test, Chi-square test.Results: We found 499,029 T2DM patients and 48,902 CKD patients in 2016, and 586,075 T2DM patients and 38,347 CKD patients in 2020. The majority of all prevalent T2DM and CKD patients were older (aged 60-69 years: 34.1% and 25.8%; ≥70 years: 36.1% and 64.4%, respectively). The annual incidence of T2DM and incidence rates of CKD in T2DM decreased in 2017-2020 (p < 0.001). The annual prevalence of T2DM increased (p < 0.01), the prevalence rates of CKD in T2DM were low and decreased from 9.8% to 6.5% in 2016-2020 (p < 0.001).Conclusion: Incidence and prevalence of T2DM-associated CKD decreased significantly in Hungary in 2016-2020. Lower prevalence rates of CKD may suggest under-recognition and/or under-reporting.